2022
DOI: 10.3390/ijerph19084916
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Risks Associated with Foot and Ankle Injuries in Ballet Dancers: A Systematic Review

Abstract: Professional ballet dancers can be classified as dance artists and sports performers. This systematic review aims to consider the biomechanical risk factors for foot and ankle injuries in ballet dancers, as this could potentially reduce the impact that ‘cost of injury’ may have on ballet companies. An additional outcome was to examine the effects of injury on the career of ballet dancers. This study searched articles in four electronic databases for information in peer-reviewed journals. The included articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In addition, assessing the mechanism of injury by injury pathology type revealed that the primary mechanism of injury of ankle sprains was jumping activities but the primary mechanisms of ankle synovitis and impingement in women were related to dancing en point e. Previous biomechanical research studies have shown that pointe shoes, overuse of the lower extremity, and the biomechanics and function of the foot are risk factors associated with foot and ankle injuries in ballet dancers. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, assessing the mechanism of injury by injury pathology type revealed that the primary mechanism of injury of ankle sprains was jumping activities but the primary mechanisms of ankle synovitis and impingement in women were related to dancing en point e. Previous biomechanical research studies have shown that pointe shoes, overuse of the lower extremity, and the biomechanics and function of the foot are risk factors associated with foot and ankle injuries in ballet dancers. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous biomechanical research studies have shown that pointe shoes, overuse of the lower extremity, and the biomechanics and function of the foot are risk factors associated with foot and ankle injuries in ballet dancers. 23 Biomechanical research targeting pointe and jumping actions with their relationship to specific injuries may contribute to improve injury-prevention strategies. Several research studies have been conducted on the biomechanics of jumping and landing in ballet dancers, 24 and dancers have been reported to have different jumping and landing strategies compared with other athletes.…”
Section: Cause Of Injuriesmentioning
confidence: 99%
“…In elite, pre-professional and professional dancers the range of motion of these movements can go up to 90 degrees. 28,29 Dancers use the foot to reach extreme external rotations while the ankle needs to twist either on the air or on the ground, as a result, the stress placed in this joint leads to a higher risk of injury. Also, during pointe positions, the dancers have a reduced base of support, causing an overload in the joint, ligaments and muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its own structural characteristics and the heavy load borne by it, the ankle is particularly prone to injuries in sports. Many people suffer from ankle injuries and loss of normal activity function annually due to sports injuries, strokes, and ankle diseases [2]. Medical research indicates that scientific and effective rehabilitation training can accelerate the healing of damaged tissues, help restore ligament elasticity, and prevent joint adhesion [3].…”
Section: Introductionmentioning
confidence: 99%